Organ-Specific Immune-Related Adverse Events Associated With Immune Checkpoint Inhibitor Monotherapy Versus Combination Therapy in Cancer: A Meta-Analysis of Randomized Controlled Trials - Da, Lijun; Teng, Yuanjun; Wang, Na; Zaguirre, Karen; Liu, Yating; Qi, Yali; Song, Feixue (Frontiers in Pharmacology, 2020)
Background Although combination therapy with immune checkpoint inhibitors (ICIs) provides a promising efficacy in multiple cancers, their use is facing challenges for a high incidence of adverse effects. This meta-analysis was conducted to compare the risks of organ-specific immune-related adverse events (IRAEs) associated with ICI monotherapy versus combination therapy among cancer patients. Methods Electronic databases were systematically searched to include eligible randomized controlled trials (RCTs). Any-grade and 3-5 grade IRAEs (colitis, pneumonitis, hepatitis, hypothyroidism, hyperthyroidism, and hypophysitis) were extracted for meta-analysis. Two reviewers independently assessed the methodological quality. The RevMan 5.3.5 software was used for meta-analysis. Results A total of 10 studies involving 8 RCTs with 2716 patients were included in this study. The most common any-grade adverse event was colitis (14.5%), followed by hypothyroidism (13.8%), hepatitis (10.4%), hypophysitis (10.0%), hyperthyroidism (9.3%), and pneumonitis (4.6%). Meta-analysis showed that ICI combination therapy significantly increased the risks of any-grade IRAEs in colitis [relative risk (RR), 3.56; 95% confidence interval (CI), 1.56–8.12; p < 0.05], pneumonitis (RR, 2.31; 95% CI, 1.54–3.45; p < 0.05), hepatitis (RR, 2.54; 95% CI, 1.65–3.91; p < 0.05), hypothyroidism (RR, 2.17; 95% CI, 1.71–2.76; p < 0.05), hyperthyroidism (RR, 3.13; 95% CI, 2.08–4.70; p < 0.05), and hypophysitis (RR, 3.54; 95% CI, 2.07–6.07; p < 0.05) compared with ICI monotherapy, as well as 3-5 grade IRAEs in colitis (RR, 2.50; 95% CI, 1.62–3.86; p < 0.05), pneumonitis (RR, 1.99; 95% CI, 1.00–3.93; p = 0.05), and hepatitis (RR, 2.70; 95% CI, 1.29–5.63; p < 0.05). Conclusions This meta-analysis demonstrated that, compared with ICI monotherapy, patients receiving ICI combination therapy significantly increased organ-specific IRAEs in colitis, hypothyroidism, hepatitis, hypophysitis, hyperthyroidism, and pneumonitis. The incidence and severity of organ-specific IRAEs were drug and dose independent.